HIV ascertainment through repeat home-based testing in the context of a Treatment as Prevention trial (ANRS 12249 TasP) in rural South Africa - (:unkn) unknown (My University, 2014)
BackgroundThe ANRS 12249 TasP cluster-randomised trial evaluates whether HIV testing of all members of a community, followed by immediate antiretroviral treatment (ART) for infected people, will prevent onward sexual transmission and reduce HIV incidence at population level. Ascertaining the HIV status of a high proportion of the population regularly and repeatedly is key to the success of any universal test and treat strategy, as the first step of the HIV cascade.MethodsBetween March 2012 and March 2014, we implemented three six-monthly rounds of home-based HIV counselling and testing in ten local communities (clusters). At each home visit, individual questionnaires were administered and a rapid HIV test offered to all trial participants. We report early results on rates of HIV ascertainment, defined as undergoing a rapid HIV test or HIV-positive self-report.ResultsOf 12,911 eligible individuals (resident in the trial area and ≥16 years), 10,007 were successfully contacted at least once. At first contact, HIV status was ascertained for 7,628 (76.2% [95% CI: 75.4-77.1]) individuals. At second contact, among the 5,885 individuals contacted a second time, HIV status was ascertained for 2,829 (85.0% [95% CI: 83.7-86.2]) of the 3,328 tested negative at first contact and for 543 (45.7% [95% CI: 42.9-48.6]) of the 1,188 who refused a rapid test at first contact. Overall, HIV ascertainment rate was 89.0% (5,239/5,885 [95% CI: 88.2-89.8]) among trial participants contacted twice.ConclusionsRepeat home-based HIV testing is acceptable and feasible in this rural area. Socio-demographic characteristics, behaviours, attitudes, household characteristics and experience of HIV infection and ART in the household will be explored for their association with HIV ascertainment uptake. This will inform whether this intervention reaches the individuals at higher risk in a rural South African region.
Keywords: African Research